2016
DOI: 10.1155/2016/8418613
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Corneal Biomechanics, Anterior Segment Parameters, and Geometric Corneal Parameters

Abstract: Purpose. To investigate the relationship between corneal biomechanical parameters, anterior segment parameters, and geometric corneal parameters in a healthy Caucasian group. Methods. This retrospective study included the healthy eyes with best corrected visual acuity of at least 20/40 of 122 Caucasian subjects. The anterior segment parameters and geometric corneal parameters such as corneal volume, central corneal thickness, horizontal and vertical corneal radii, anterior and posterior steep, and flat keratom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
9
1
1
Order By: Relevance
“…CH and CRF in the current study showed no signi cant association with ACD and ACV in all eyes which agreed with Hwang et al 7 However, this nding was not in agreement with Çevik et al 2016 10 who reported positive associations between ACD and CRF and Chang et al 13 who con rmed a signi cant association between ACD measured by the IOLMaster and CH only not CRF. On the other hand, mild myopic eyes (63 eyes) in our study showed a highly signi cant positive correlation between IOP g and ACV.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…CH and CRF in the current study showed no signi cant association with ACD and ACV in all eyes which agreed with Hwang et al 7 However, this nding was not in agreement with Çevik et al 2016 10 who reported positive associations between ACD and CRF and Chang et al 13 who con rmed a signi cant association between ACD measured by the IOLMaster and CH only not CRF. On the other hand, mild myopic eyes (63 eyes) in our study showed a highly signi cant positive correlation between IOP g and ACV.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, the association between ORA parameters and keratometric values for mild myopic eyes (63 eyes) in this study found a signi cant positive correlation between ASKV and each of CH and CRF. Çevik et al 2016 10 reported a negative correlation between CH, CRF with both posterior steep and average posterior values. Furthermore, many studies 7,8,9,[13][14][15][16][17] reported an association between mean k and CH only.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Protože je CCT pozitivně korelována s tuhostí rohovky (tlustší rohovky jsou i tužší, viz např. [5,35,5]), lze na základě vzájemného vztahu pokládat vliv CCT pozorovaný v naší i v jiných studiích za odraz vlivu tuhosti rohovky. Měření CH však nebylo do této práce zahrnuto.…”
Section: Diskuseunclassified